Notes to Make the Sound Come Right : Four Innovators of Jazz Poetry - Anderson, T. J., III, 1958- (Book collections on Project MUSE., 2004)
"In this book, T.J. Anderson, son of the brilliant composer, Thomas Anderson, Jr., asserts that jazz became in the twentieth century not only a way of revising old musical forms, such as spiritual and work song, but also a way of examining the African American social and cultural experience. He traces the growing history of jazz poetry and examines the work of four innovative and critically acclaimed African American poets whose work is informed by a jazz aesthetic: Stephen Jonas (1925?-1970) and the unjustly overlooked Bob Kaufman (1925-1986), who have affinities with Beat poetry; Jayne Cortez (1936- ), whose work is rooted in surrealism; and the difficult and demanding Nathaniel Mackey (1947- ), who has links to the language writers. Each fashioned a significant and vibrant body of work that employs several of the key elements of jazz."--Jacket